2014
DOI: 10.1093/icvts/ivu343
|View full text |Cite
|
Sign up to set email alerts
|

Routine thymectomy in congenital cardiac surgery changes adaptive immunity without clinical relevance

Abstract: The actual importance of the thymus in both children and adults is largely unclear. In congenital cardiac surgery, a partial or total thymectomy is frequently performed to improve access to the heart and great vessels. We performed a literature search to evaluate the effect on the adaptive immune system of the removal of thymus tissue in patients with congenital heart disease. A PubMed search according to Dunning's standard provided 149 articles, of which 13 addressed our search question. Each study has been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Even though we detected a skewed autoantibody profile after neonatal Tx in early life, in line with previous observations there were no signs of clinical autoimmune disease . Evaluation of specific autoantibodies after Tx was previously assessed, but none of these children had measurable ANA .…”
Section: Discussionsupporting
confidence: 91%
“…Even though we detected a skewed autoantibody profile after neonatal Tx in early life, in line with previous observations there were no signs of clinical autoimmune disease . Evaluation of specific autoantibodies after Tx was previously assessed, but none of these children had measurable ANA .…”
Section: Discussionsupporting
confidence: 91%
“…The minimal residual thymic tissue was sufficient for immune function. In a meta-analysis made by Roosen et al 26 , it was suggested that the thymectomy was responsible for immunological alterations, reduced proportions of RTE and lower numbers of naive T cells. van Gent et al 27 described the impact of thymectomy during early childhood over three decades; so the presence of new TREC-containing naive T cells was suggestive of thymic regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Total thymectomy in early infancy has effects on circulating T‐cell pools for up to 5 years post‐procedure. However, the functional and clinical significance of this state is unclear, and live vaccination efficacy and safety are unknown . Thymectomy is thought to be rare in kidney and liver transplant recipients.…”
Section: Outcomementioning
confidence: 99%